THE INFLUENCE OF GCG APPLICATION, COMPANY SIZE, and PROFITABILITY ON STOCK RETURN - Octavia, Evi; Alethea, Nabila; Ristanti, Helmi (International Journal of Psychosocial Rehabilitation, 2020)
This study shows that the size of the company affects the stock returns of state-owned companies listed on the Stock Exchange in the period 2013-2017, this shows that the greater the size of a company, the higher the level of stock returns obtained by investors. While the proportion of independent commissioners, audit committees, government share ownership, foreign share ownership, and ROAs partially does not affect stock returns. But the proportion of independent commissioners, audit committees, government share ownership, foreign share ownership, company size, and ROA simultaneously influence the stock returns of state-owned companies listed on the IDX in 2013-2017